Disseminated Juvenile Xanthogranuloma and Hemophagocytic Lymphohistiocytosis Developed During Treatment of Acute Lymphoblastic Leukemia: Case Report - Pawińska-Wa̧sikowska, Katarzyna; Cwiklinska, Magdalena; Wyrobek, Elzbieta; Balwierz, Walentyna; Bukowska-Strakova, Karolina; Dluzniewska, Agnieszka; Gozdzik, Jolanta; Drabik, Grazyna; Rygielska, Monika; Stepien, Konrad; Skoczen, Szymon (Frontiers in Oncology, 2020)
The association between acute lymphoblastic leukemia (ALL), non-Langerhans cell histiocytosis (non-LCH) and hemophagocytic lymphohistiocytosis (HLH) to the best of our knowledge, has not been published to date. The juvenile xanthogranuloma (JXG), as a type non-Langerhans cell histiocytosis, is usually a benign disease limited to the skin. Systemic involvement is rarely reported. The present case report describes a 15-year-old boy diagnosed with disseminated JXG involving skin and bone marrow concurrent with severe symptoms of HLH during ALL therapy. Examination of immunoglobulin heavy chain genes in B-cell precursor leukemic blasts and histiocytes in the skin and bone marrow revealed identical rearrangements, confirming clonal relationship between both diseases. Implementation of corticosteroids, vinblastine, etoposide, cyclosporine and tocilizumab resulted in partial skin lesions resolution with no improvement of bone marrow function, therefore hematopoietic stem cell transplantation (HSCT) was eventually performed. The patient's hematological and general status has improved gradually, however, remarkable recovery of skin lesions was observed after empirical antitubercular therapy. Mycobacterium spp. infection should be considered as possible secondary HLH trigger. Triple association of ALL, non-LCH and HLH highlights heterogeneity of histiocytic disorders and possible common origin of dendritic and lymphoid cell. .